36th Malaysian Society of Pharmacology and Physiology Annual Scientific Meeting 2023 - Balan, Santhra Segaran; Basir, Rusliza; Yong, Yoke Keong; Mohammed Izham, Noor Aishah; Chia, Jasmine Siew Min; Othman, Fezah; Lim , Jonathan Chee Woei; Md Tohid, Siti Farah; Bahari, Hasnah; Tham, Chau Ling (Life Sciences, Medicine and Biomedicine, 2023)
The 36th Malaysian Society of Pharmacology and Physiology (MSPP) Annual Scientific Meeting was hosted in collaboration with the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia from the 7th to 8th of August 2023 at Bangi Resort Hotel in Bangi, Malaysia. The event focused on the theme "Pharmacology & Physiology Post-Millenial Era: Challenges & Opportunities". This platform is one of the suitable avenues to facilitate the exchange of scientific endeavors and enhance networking among scientists, academicians, clinicians, and postgraduate students involved in the fields of pharmacology and physiology, as well as multidisciplinary areas such as drug discovery, omics approaches, stem cells, and regenerative medicine. The primary objective of the special issue is to revitalize recent advances and breakthroughs in pharmacology and physiology to enhance opportunities and vanquish challenges in the post-millenial era, especially in the wake of the COVID-19 pandemic. In light of this, the special issue compiles the conference proceeding, to provide opportunities for knowledge integration of research and innovations.